Dual Mode of Education and Prospects in Tertiary Level: Perspective the Private Universities in Bangladesh - Chowdhury, Muktasha Deena (Asian Business Review, 2022)
Due to the COVID-19 pandemic, many educational institutes in Bangladesh were forced to adopt online technologies for conducting their classes and examinations. Internet-based video conferencing applications, such as Zoom, google-meet, Facebook Messenger, etc., became especially useful during the quarantine days. Within a few months, almost all private and public universities started conducting online classes without much directive or pressure from the government. Within a short period, all stakeholders, including teachers, students, and management, get used to these new systems despite many challenges. This study aims to focus advantages of online education over classroom education for effective learning for university-level students. This study tries to identify the advantages and disadvantages of this online-based education system over the classroom-based system at the tertiary education level. Data was collected from 400 students from different private universities in Bangladesh using a Stratified sampling technique. Results show that the most crucial advantage is the participation of students in the class, i.e., students' attendance. Other benefits are reduced costs, systematic arrangement of study materials, and mental peace for working students as they could continue studying and doing jobs simultaneously. Vis-à-vis the study reveals disadvantages like 'conducting the fair examination,' availability, affordability, and internet reliability. Finally, the study suggests that “a combination of online-based education and classroom-based examination," i.e., dual mode of education, can increase the percentage of student enrollment in tertiary education without compromising quality.
Keywords: Dual Mode of Education; Tertiary level; e-learning; Educational Technology